2006
DOI: 10.2991/jnmp.2006.13.4.11
|View full text |Cite
|
Sign up to set email alerts
|

The Heun equation and the Calogero-Moser-Sutherland system V: generalized Darboux transformations

Abstract: We obtain isomonodromic transformations for Heun's equation by generalizing the Darboux transformation, and we find pairs and triplets of Heun's equation which have the same monodromy structure. By composing generalized Darboux transformations, we establish a new construction of the commuting operator which ensures that the finite-gap property is satisfied. As an application, we prove some previous conjectures in part III.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
95
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 26 publications
(95 citation statements)
references
References 19 publications
0
95
0
Order By: Relevance
“…Then the mean field equations Proof. It was proved by Takemura [26,Section 4] that H((n, 0, 0, 0), B, τ) and H((n 0 , n 1 , n 2 , n 3 ), B, τ) are isomonodromic (i.e. their monodromy representations are the same) for any (B, τ).…”
Section: Define the Wronskianmentioning
confidence: 99%
“…Then the mean field equations Proof. It was proved by Takemura [26,Section 4] that H((n, 0, 0, 0), B, τ) and H((n 0 , n 1 , n 2 , n 3 ), B, τ) are isomonodromic (i.e. their monodromy representations are the same) for any (B, τ).…”
Section: Define the Wronskianmentioning
confidence: 99%
“…Finite-gap integration is applicable for the case γ, δ, , α − β ∈ Z + 1/2, t ∈ C \ {0, 1} and all q, and results on the integral representation of solutions [13], the Bethe Ansatz [13], the Hermite-Krichever Ansatz [1,16], the monodromy formulae by hyperelliptic integrals [15], the hyperelliptic-to-elliptic reduction formulae [16] and relationships with the Darboux transformation [17] have been obtained. In this paper, we obtain integral formulae of solutions for the case γ, δ, , α + 1/2, β + 1/2 ∈ Z, t ∈ C \ {0, 1} and all q, which then facilitates a calculation of the monodromy.…”
Section: Introductionmentioning
confidence: 99%
“…Other examples of the finite-gap potential were found by Treibich andVerdier. Around 1987-1992, they found that the potential P 3 iZ0 l i ðl i C 1Þ §ðx C u i Þ (u 0 Z0, u 1 Z1/2, u 2 ZK(tC1)/2 and u 3 Zt/2), which is called the Treibich & Verdier (1992) potential, is an algebro-geometric finite-gap potential iff l i 2Z for all i2{0, 1, 2, 3}. They proved it by using a theory of elliptic soliton, which is closely related to the geometry of Riemann surfaces.…”
Section: Introductionmentioning
confidence: 78%
“…(ii) (The case l 0 Z2,l 1 Z1,l 2 Z0,l 3 Z1) The functionsL 1 ðw; qÞ,L 2 ðw; qÞ,QðqÞ, Q 1 ðqÞ andQ t ðqÞ are calculated as follows: (Takemura 2005) and Darboux transformation (Takemura 2006b). Consequently, conjectures 3.1 and 3.2 were proved.…”
mentioning
confidence: 99%